2019
DOI: 10.7717/peerj.7480
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of Fritillaria cirrhosa D. Don and its closely related species based on complete chloroplast genomes

Abstract: Fritillaria cirrhosa D. Don, whose bulb is used in a well-known traditional Chinese medicine to relieve cough and eliminate phlegm, is one of the most important medicinal plants of Fritillaria L. The species is widely distributed among the alpine regions in southwestern China and possesses complex morphological variations in different distributions. A series of newly related species were reported, based on obscure morphological differences. As a result, F. cirrhosa and its closely related species constitute a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 89 publications
(117 reference statements)
2
27
0
Order By: Relevance
“…Only seven hypervariable intergenic regions were selected as potential specific DNA barcode based on comparison of four Fritillaria cp genomes. Similar results existed in other studies [ 58 – 64 ], except that the number of highly variable regions was different. Unfortunately, none of the above regions have been verified by further experiments.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Only seven hypervariable intergenic regions were selected as potential specific DNA barcode based on comparison of four Fritillaria cp genomes. Similar results existed in other studies [ 58 – 64 ], except that the number of highly variable regions was different. Unfortunately, none of the above regions have been verified by further experiments.…”
Section: Discussionsupporting
confidence: 90%
“…In order to find ideal molecular markers in Fritillaria , many studies tried to select highly variable regions based on cp genomes as genus-specific DNA barcodes for species identification [ 56 64 ]. Li et al [ 56 ] found eight genes which had abundant variations among species by comparing four Fritillaria cp genomes.…”
Section: Discussionmentioning
confidence: 99%
“…The extent and types of genetic polymorphisms in different regions of the cp genome vary. In most plants, the single copy regions (LSC and SSC regions) of the cp genome are more variable than that are the IR regions [ 16 , 41 , 42 ]. In our study, nucleotide diversity, as quantified by Pi values across the six Desmodieae cp genomes, for SSC and LSC was 0.02752 and 0.02146, respectively, both of which were significantly higher than the Pi value for the IR regions (0.00374).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with nuclear genomes, cp genomes in Fabaceae are uniparentally inherited and largely conserved in gene content, organization, and structure [ 13 , 14 ]. Due to its stable uniparental inheritance, the cp genome can be of great value for discriminating between closely related species and understanding their evolutionary relationships [ 15 , 16 , 17 ]. With the development of next-generation sequencing (NGS), complete plastome sequencing has increased dramatically.…”
Section: Introductionmentioning
confidence: 99%
“…Cp genomes are haploid, and most of them are maternally inherited. High conservation of gene content and genome structure makes cp genome an important resource for reconstructing the phylogenetic relationships among plant groups [13][14][15][16][17][18][19][20], which may suggest that the cp genome could be better to solve the relationships between species [21][22][23]. Additionally, the cp genome encodes many chloroplast-specific components, like photosynthesis genes, which play fundamental roles in the life of plant [24][25][26].…”
Section: Introductionmentioning
confidence: 99%